Intra-Diverticular Bladder Tumours: How to Manage Rationally - Mohammed Lotfi Amer; Hassan Mumtaz; Beth Russell; Jason Gan; Zahra Rehman; Rajesh Nair; Ramesh Thurairaja; Muhammad Shamim Khan (Société Internationale d’Urologie Journal, 2022)
ObjectiveTo report changing practice in the management of intra-diverticular bladder tumours. MethodsWe undertook a review of all intra-diverticular bladder tumours in our prospectively maintained institutional database. ResultsA total of 28 patients (male = 27, female = 1) with a median age of 71 years (IQR 61 to 76) were diagnosed with intra-diverticular bladder tumours (IDBT) between March 2013 and February 2021. Fourteen had visible and 3 had non-visible haematuria, while 11 patients had lower urinary tract symptoms. Median axial diameter of the diverticula was 46 mm (IQR 35 to 69), and median neck diameter was 9 mm (IQR 7 to 11). All patients had CT-urography and 5 patients also had an MRI. Surgical treatment consisted of diverticulectomy (n = 11), diverticulectomy and ipsilateral ureteric reimplantation (n = 11), radical cystectomy and ileal conduit (n = 4), or radical cystectomy and orthotopic bladder (n = 2). Eleven patients had open procedures, and 17 had robotic assisted surgery.Final pathological stages were T0 (n = 2), Ta (n = 5), T1 (n = 7), T3a (n = 8) and T3b (n = 6). Twenty-four patients had urothelial carcinoma (including one nested variant and 4 with squamous differentiation) and 2 had small cell carcinoma. Three patients had neoadjuvant systemic chemotherapy, 2 had intravesical bacillus Calmette-Guerin (BCG) with mitomycin, and one had BCG monotherapy preoperatively. Five patients had adjuvant systemic chemotherapy while 7 had adjuvant intravesical therapies. Mean follow-up period was 37.8 months (±25.3). Mean recurrence-free survival was 61.5% (CI 45.7 to 77.4) and mean overall survival 71.6 % (CI 57.4 to 85.8). Ten patients (37%) died of cancer. ConclusionManagement of intra-diverticular bladder tumours is evolving. Bladder-sparing approaches are gaining popularity. Robot-assisted diverticulectomy is preferable as it reduces the morbidity resulting from treatment